Mechanical properties of recycled aggregate concrete surface treated by variation in mixing approaches - Jagan, S.; Neelakantan, T. R.; Saravanakumar, P. (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Increased demand for natural aggregates (NA) due to infrastructural development has necessitated the use of alternative aggregates in the field of construction. One such option is the utilization of construction and demolition wastes, preferably named as recycled coarse aggregates (RCA) to produce a sustainable recycled aggregate concrete (RAC). Perhaps, the quality of RCA is usually poor due to the presence of adhered mortar on its surface affecting the strength and durability properties of RAC. Consequently, it is essential to improve the behavior of recycled aggregate concrete. In order to improve the recycled concrete aggregate, four different processing techniques such as two-stage mixing approach (TSMA), mortar mixing approach (MMA), sand enveloped mixing approach (SEMA) and double mixing approach (DMA) were used to improve the quality of RAC. This paper aims at providing a comparative study on the suitability of different mixing approaches and their influence over the fresh and hardened properties of recycled aggregate concrete. The performance behaviour of RAC was evaluated at 7, 14, 28 and 90 days with various percentage replacements of RCA at w/c ratios of 0.45 and 0.5. Experimental results indicate that the strength of concrete made of 100% RCA was equivalent to the target strength at 90 days. Also, among the various mixing processing techniques, MMA shows better fresh and hardened properties of concrete at different curing ages. Micro-structural investigations through SEM were performed to investigate the modification in the ITZ of the RAC through MMA approach.